2006
DOI: 10.1001/archpsyc.63.7.769
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Transporter Gene SLC1A1 Associated With Obsessive-compulsive Disorder

Abstract: Although requiring replication in larger samples, these findings provide preliminary evidence that sequence variation in SLC1A1 is associated with susceptibility to OCD, particularly in males. Furthermore, these results provide support for the role of altered glutamatergic neurotransmission in the pathogenesis of OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
213
3
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(241 citation statements)
references
References 51 publications
19
213
3
4
Order By: Relevance
“…At least two other genes affecting glutamatergic neurotransmission appear associated with OCD, SLC1A1 [Arnold et al, 2006;Dickel et al, 2006;Stewart et al, 2007] and, more preliminarily, GRIN2B [Arnold et al, 2004]. Again, we found no evidence for an association of Sapap3 with OCD itself, though we cannot rule out the possibility that Sapap3 is relevant to a pathological grooming-related ''subtype'' of OCD (recall that more than 1/3 of the participants with OCD had a GD).…”
Section: Discussioncontrasting
confidence: 69%
“…At least two other genes affecting glutamatergic neurotransmission appear associated with OCD, SLC1A1 [Arnold et al, 2006;Dickel et al, 2006;Stewart et al, 2007] and, more preliminarily, GRIN2B [Arnold et al, 2004]. Again, we found no evidence for an association of Sapap3 with OCD itself, though we cannot rule out the possibility that Sapap3 is relevant to a pathological grooming-related ''subtype'' of OCD (recall that more than 1/3 of the participants with OCD had a GD).…”
Section: Discussioncontrasting
confidence: 69%
“…It should also be noted that the recent association between 5-HTTLPR and OCD by Hu et al was observed in a case-control as well as in a family-based association study, the latter of which is not susceptible to hidden population stratification. Thus, the lack of association in our study warrants further analyses in large family-based OCD samples such as the OCD Collaborative Genetics Study ) before it will point toward the need to analyze other candidate regions such as 9p, 3q, 7p, 1q, 15q, 6q, and 13q (Hanna et al, 2002;Shugart et al, 2006;Willour et al, 2004) and polymorphisms involved in other neurotransmitters such as glutamate (Arnold et al, 2006;Dickel et al, 2006;Rosenberg and Keshavan, 1998), neuromodulators, and developmental signals potentially of importance in OCD such as glutamate.…”
Section: Discussionmentioning
confidence: 84%
“…Single tests of association under additive and recessive models were assessed using the Family-Based Association Tests (FBAT) program (v. 1.7.1) [Rabinowitz & Laird, 2000]. Recessive models were included because they were used in at least one of the OCD association studies [Arnold et al, 2006]; the additive model of FBAT is presented for comparison. It should be noted that because each SNP is biallelic, the significance of the results for the recessive model is the same as the dominant model (the Z-scores for the alleles are flipped and in the opposite direction).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This finding was replicated in 42 pedigrees with early onset OCD [Willour et al, 2004]. Subsequently, three studies have reported an association between markers at SLC1A1 and OCD [Arnold, Sicard, Burroughs, Richter, & Kennedy, 2006;Dickel et al, 2006;Stewart et al, 2007a]. The Autism Genome Project, a largescale, collaborative autism genetics research project, identified SLC1A1 in a genome-wide linkage scan of autism due to its proximity to a linkage peak at 9p24.1, and its role in glutamate function [Szatmari et al, 2007].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation